1998
DOI: 10.1523/jneurosci.18-08-03014.1998
|View full text |Cite
|
Sign up to set email alerts
|

Phase Shifting of Circadian Rhythms and Depression of Neuronal Activity in the Rat Suprachiasmatic Nucleus by Neuropeptide Y: Mediation by Different Receptor Subtypes

Abstract: Neuropeptide Y (NPY) has been implicated in the phase shifting of circadian rhythms in the hypothalamic suprachiasmatic nucleus (SCN). Using long-term, multiple-neuron recordings, we examined the direct effects and phase-shifting properties of NPY application in rat SCN slices in vitro (n = 453). Application of NPY and peptide YY to SCN slices at circadian time (CT) 7.5-8.5 produced concentration-dependent, reversible inhibition of cell firing and a subsequent significant phase advance. Several lines of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 42 publications
(72 reference statements)
12
84
0
Order By: Relevance
“…Consistent with previous studies (Bouskila and Dudek, 1993;Gribkoff et al, 1998;Mrugala et al, 2000), all WT slices showed clear circadian rhythms in SCN MUA (Fig. 4a) (supplemental Figs.…”
Section: Grp Promotes Cellular Rhythmicity In the Wt Scn In The Absensupporting
confidence: 92%
“…Consistent with previous studies (Bouskila and Dudek, 1993;Gribkoff et al, 1998;Mrugala et al, 2000), all WT slices showed clear circadian rhythms in SCN MUA (Fig. 4a) (supplemental Figs.…”
Section: Grp Promotes Cellular Rhythmicity In the Wt Scn In The Absensupporting
confidence: 92%
“…Consistent with previous findings (Bouskila and Dudek 1993;Brown et al 2005Brown et al , 2006Gribkoff et al 1998;Mrugala et al 2000), all wild-type (VIP/PHI ϩ/ϩ ) slices (n ϭ 7) exhibited clear rhythms in SCN MUA ( (F) mice also show firing rate rhythms that peak during the projected day, whereas cells from VIP/PHI Ϫ/Ϫ mice (G and H) express rhythms with variable phasing (top) or are arrhythmic (bottom). All graphs show average firing rate (Hz) each minute from 1 representative slice, moderately smoothed using a 1-h moving average.…”
Section: R E S U L T Ssupporting
confidence: 89%
“…This supports earlier unpublished findings from administration of NPY in vivo (Duncan unpublished, cited in Duncan and Franklin 2007). Further, while phase shifts to NPY in the rat and hamster may require actions at GABAa receptors Gribkoff et al 1998 but see Biello et al 1997a, b) our work here would suggest that resetting to NPY in the mouse may not, as phase shifts to the GABAa agonist muscimol was decreased with age, while phase shifts to NPY remain unaltered. Phase shifts to NPY are thought to be mediated by the Y2 receptor (Golombek et al 1996;Huhman et al 1996), while attenuation of photic stimuli by NPY are mediated by the Y5 receptor (Gamble et al 2005;Yannielli et al 2004).…”
Section: Discussionmentioning
confidence: 49%